2018
DOI: 10.1111/1751-2980.12613
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock protein family A member 6 combined with clinical characteristics for the differential diagnosis of intestinal Behçet’s disease

Abstract: HSPA6 in combination with clinical, radiological and pathological characteristics is useful in distinguishing intestinal BD from CD with ileocolonic involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Studies found that over half of intestinal BD patients were misdiagnosed as having CD at their first visit. Significant clinical similarities may contribute to the high rate of misdiagnosis (10). Consistent with past experience, there are factors leading to misdiagnosis between intestinal BD and CD.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Studies found that over half of intestinal BD patients were misdiagnosed as having CD at their first visit. Significant clinical similarities may contribute to the high rate of misdiagnosis (10). Consistent with past experience, there are factors leading to misdiagnosis between intestinal BD and CD.…”
Section: Discussionsupporting
confidence: 62%
“…It is easily misdiagnosed because there are no specific pathological or laboratory markers for the diagnosis of the entity. Several case reports and clinical studies highlighted the difficulties in making this distinction (5,(10)(11)(12)(13). To date, several discriminating endoscopic findings have been reported, including round shape, five or fewer lesions, focal distribution, and absence of aphthous and cobblestone lesions as features supporting the diagnosis of intestinal BD (12).…”
Section: Discussionmentioning
confidence: 99%
“…HSPs and lipopolysaccharides (LPS) of microbial agents were frequently noted in the involved organs of BD patients. [27][28][29][30] It is suggested that microorganisms' HSPs and the LPS cross-reaction with human antigens leads to the innate immune activation and inflammatory response. 31,32 TLR4 can be involved in the pathology of BD by recognizing HSPs and LPS.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial agents have a crucial function in the pathology of BD. HSPs and lipopolysaccharides (LPS) of microbial agents were frequently noted in the involved organs of BD patients 27–30 . It is suggested that microorganisms' HSPs and the LPS cross‐reaction with human antigens leads to the innate immune activation and inflammatory response 31,32 .…”
Section: Discussionmentioning
confidence: 99%
“…There was no correlation between HSPA6 expression levels and oral ulcers, genital ulcers, or disease activity among Crohn’s disease patients. 65 Additionally, Lee et al 66 found increased HSP27 and decreased HSP60 protein expression levels in 17 BS patients compared to 17 healthy controls, using two-dimensional (2D) electrophoresis and MALDI-TOF/TOF MS methods.…”
Section: Heat Shock Proteins In Behçet Syndromementioning
confidence: 99%